Flavored Self Microemulsifying Lipid Formulations for Masking the Organoleptic Taste of Pharmaceutical Actives - Naser M Hasan, Melfi S Al-aram, Mohammed S Al-wadie, Fahad A Althobaiti, Majed J Al-Malki (Journal of Applied Pharmaceutical Science, 2015)
The field of SMEDDS is designed to enhance bioavailability of poorly-water soluble compounds. Yet, these systems have the capacity to solubilize aqueous-based materials within its lipid matrix as L2 phase (W/O microemulsion). This characteristic is utilized in this investigation to incorporate aqueous flavors within oil vehicle as an approach to mask bitter taste of drugs. Miscibility profiles and self-micro-emulsifying regions for various lipid composites were screened by constructing ternary phase diagrams using different types of oil, cosurfactant and surfactant. Solubility of bitter taste model drug was measured in various optimized vehicles. Dynamic equilibrium phase studies were performed and phase boundaries were determined for the lipid-aqueous flavors-water systems. Self-micro-emulsifying system comprising Crodamol GTCC/ Glycerox 767HC /Croduret 40 ss at ratios of {0/80/20}, {6/54/40} or {10/40/50} have shown capacity to solubilize, aqueous-based materials including; strawberry flavor, sucrose and citric acid as L2 phase. Phase behavior study has revealed that clear dispersions can be obtained at all dilutions with water. Potential flavored self-microemulsifying lipid formulations representing type III lipid class system were developed. Aqueous flavors loaded into these vehicles can be used to mask bitter tastes in oral pharmaceuticals.
Keywords: SMEDDS, Lipid formulations,Micro-emulsion, Taste masking, Bitter taste drugs.